An Efficient and Convenient Protocol for the Synthesis of 1,1-Difluoro-6-nitro-2,3-dihydro-1H-indene Derivatives - Zhang, Dongfeng; Li, Peng; Lin, Ziyun; Huang, Haihong (Synthesis, 2014)
A convenient and efficient synthesis of gem-difluorinated compounds is reported. The synthetic route toward various 2-substituted and 3-substituted 1,1-difluoro-6-nitro-2,3-dihydro-1H-indene derivatives is described starting from commercially available indanone. The key gem-difluorination step is accomplished in good yield by treatment of in situ generated bromine fluoride (BrF) with a dithioketal. A plausible mechanism discussing the competition between substitution and elimination is provided to rationalize the outcome of the reactions of the 3-brominated compounds with different amines.
Keywords: indanone; dithioketal; gem-difluorination; substitution; synthesis